Revision of Afrotropical Dyscritobaeus Perkins, 1910 (Hymenoptera: Scelionidae) - Tortorici, Francesco; Caleca, Virgilio; Noort, Simon Van; Masner, Lubomir (Zootaxa, 2016)
A revision of Afrotropical species of Dyscritobaeus Perkins is presented with re-description of the four known species (D. bicolor O’Connor et Ashe, D. comitans Perkins, D. parvipennis (Dodd) and D. sulawensis Mineo, O’Connor et Ashe) and description of six new species (D. antananarivensis Tortorici et Caleca sp. nov., D. flavus Tortorici et Caleca sp. nov., D. kilimanjarensis Tortorici et Caleca sp. nov., D. madagascarensis Tortorici et Caleca sp. nov., D. ndokii Tortorici et Caleca sp. nov. and D. tanzaniensis Tortorici et Caleca sp. nov.). Dyscritobaeus cerosus is considered to be a junior synonym of D. comitans, D. hannibal is considered to be a junior synonym of D. sulawensis and D. maputanus is a junior synonym of D. parvipennis; so far these species are the only three Dyscritobaeus species that are widely distributed across four zoogeographical regions: Afrotropical, Australian, Oriental and Palearctic. Dyscritobaeus comitans and D. ndokii Tortorici et Caleca sp. nov. belong to the comitans-group, the other eight species belong to the orientalis-group. Dyscritobaeus antananarivensis Tortorici et Caleca sp. nov., D. madagascarensis Tortorici et Caleca sp. nov. and D. sulawensis are morphologically similar to D. orientalis bearing the specillum on T2; D. bicolor, D. flavus Tortorici et Caleca sp. nov., D. kilimanjarensis Tortorici et Caleca sp. nov., are morphologically similar to D. parvipennis; D. tanzaniensis Tortorici et Caleca sp. nov. shares the lack of a protruding metascutellum together with D. aspinosus Mineo, O’Connor et Ashe. Dyscritobaeus species are sexually dimorphic, particularly in the following features: the anterior and posterior fringes of the fore wing are longer in the female than in the male; the odontoid process, when present in females, is less developed or absent in the corresponding males; the specillum, when present in females, is less defined and smaller or absent in the corresponding males; the sculpture of the head is more evident in males than in females; and the first and second tergites are frequently lighter in males than in females.